Evaluation of Buccal Bone Concavity in the Esthetic Zone: A Cadaver Study. Issue 5 (October 2017) - Chung, Ming-Pang; Wang, I-Ching; Chan, Hsun-Liang; Wang, Hom-Lay
Abstract : Purpose: The primary aim of this study was to evaluate the buccal bone concavity position and depth in the anterior maxilla. The accuracy of cone beam computed tomography (CBCT) to measure the buccal bone concavity was also investigated. Material and methods: Eleven fresh cadaver heads were used in this study. CBCT images were first acquired, on which the location and depth of the buccal bone concavity were measured in maxillary incisors and canines. After full-thickness mucoperiosteal flap reflection, the corresponding measurements were made directly on cadavers. The accuracy and correlations between direct and image-derived measurements were analyzed statistically. Results: A total of 53 sites were measured. The mean depths were 2.88 ± 1.37 mm and 2.40 ± 1.29 mm (with direct and CBCT measurement, respectively). The deepest concavities were found in the lateral incisors sites (3.15 ± 1.32 mm). There was a statistically significant underestimation of the depth of concavity (0.2 to 0.6 mm) by CBCT. Nevertheless, there is a high statistical correlation (r = 0.8) between the direct and CBCT measurements. Conclusions: Within the limitations of this study, it can be concluded that buccal bone concavity is the most prominent at the lateral incisor sites. The CBCT readings were highly correlated but underestimated to the direct measurements.